A terrain-adaptive robot prototype designed for bumpy-surface exploration. (November 2019) - Zhang, Fei; Yu, Yang; Wang, Qi; Zeng, Xiangyuan; Niu, Hanqing
Highlights: Propose a new kind of deformable terrain-adaptive robot, and validate its adaptability in simulation and experiment. Analyze the kinemics characters and construct the dynamic modeling of the prototype which can capture the sliding tendency and the shake of vertexes when contacting. Design different gaits for several typical terrains using the dynamic model, and validate the gaits via prototype experiments. Abstract: This paper proposes a deformable polygonal robot, aiming at high flexibility for crawling on rough terrain. A planar prototype is first developed to perform laboratory tests on a two-dimensional track. The shape of this prototype is continuously changed by the driving servos, and this determines the locomotion of the robot over a given terrain. A dynamic model considering the contact forces is applied to evaluate the performance of different gaits via simulation. Locomotion gaits are designed by kinematics, and validated first through dynamic simulation, and then by experiments. Based on the prototype, we carried out a series of laboratory experiments on several typical terrains, including slopes, obstacles, and steps. Results from simulations and experiments show that the robot is highly capable of adapting to complex terrains.